Age-Related Changes in Culm Respiration of Phyllostachys pubescens Culms With Their Anatomical and Morphological Traits - Uchida, Eiko M.; Katayama, Ayumi; Yasuda, Yuko; Enoki, Tsutomu; Otsuki, Kyoichi; Koga, Shinya; Utsumi, Yasuhiro (Frontiers in Forests and Global Change, 2022)
Compared to trees, surprisingly little is known about the respiratory characteristics of bamboo, especially culm respiration. In this study, we measured the respiration rates of current year, 2, 3, and above 4-year-old Moso bamboo (Phyllostachys pubescens) culms and examined its relation to culm morphology and anatomical structure. Current year culms had substantially higher respiration rates (1.9 ± 0.46 µmol m-2s-1) compared to older culms (2, 3, and above 4-year-old average: 0.17 ± 0.09 µmol m-2s-1). Culm wall density increased with age, with the concurrent thickening of parenchyma cell walls in the culm tissue. Nitrogen content in the culm tissue decreased with culm age. Both culm wall density and nitrogen content had significant relationships with culm respiration rate. On the other hand, culm height, wall thickness and circumference did not affect culm respiration rate. Although bamboo culms do not change in size through the year, anatomical changes in the culm tissue that accompany the aging of a culm affected the respiration. Our results suggested that young culms required a large amount of respiration to grow "inward" as cell wall thickening and also to maintain the relatively live and active state of the tissue.